Student conceptions of the production of cow's milk—An exploratory interview study with 6th- and 10th-grade students - Szczepanski, Lena; Fiebelkorn, Florian; Ostermann, Gesa; Altevogt, Lisa; Folsche, Elena (Frontiers in Nutrition, 2023)
The production of food and the associated livestock farming contribute significantly to climate change and the global loss of biodiversity, hindering the achievement of the United Nations Sustainable Development Goals (SDGs). To promote responsible consumption and production of food (SDG 12), ensuring that students understand the production of our food, the associated livestock farming, and the interrelatedness of production and consumption is essential. Thus, Education for Sustainable Development (ESD) is an important tool for achieving the SDGs. To develop effective teaching and learning strategies to educate students about the production of food from livestock, it is important to identify students’ existing conceptions of this topic. Thus, this study examined sixth-grade (n = 4; MAge = 12 years; SDAge = 0.7 years; 50% female) and tenth-grade students’ (n = 4; MAge = 16 years; SDAge = 0 years; 50% female) conceptions of milk production, focusing on dairy farming, the milking process and techniques, and the production of cow’s milk. Semi-structured interviews were conducted with students from Osnabrück (Lower Saxony) to elicit student conceptions. The evaluation of the students' conceptions was carried out using qualitative content analysis. The results largely indicated that both sixth and tenth graders had realistic conceptions of dairy farming and the milking process and techniques. However, some students also expressed romanticized conceptions of pasture grazing and calf rearing. In addition, unrealistic statements regarding the formation of milk were identified. The conceptions of the sixth and tenth graders were compared, and with a few exceptions, no significant differences were found between the two cohorts. However, the tenth graders tended to have more differentiated conceptions about milk production than the sixth graders. In conducting the analysis, it became clear that students’ conceptions of the production of milk are influenced by individual primary experiences with dairy farms. Finally, based on these results, educational recommendations for the school teaching framework in the context of ESD and implications for further research are presented.